Depth of the biologically active zone in upland habitats at the Hanford Site, Washington: Implications for remediation and ecological risk management. (7th November 2014) - Sample, Bradley E; Lowe, John; Seeley, Paul; Markin, Melanie; McCarthy, Chris; Hansen, Jim; Aly, Alaa H
ABSTRACT Soil invertebrates, mammals, and plants penetrate and exploit the surface soil layer (i.e., the biologically active zone) to varying depths. As the US Department of Energy remediates radioactive and hazardous wastes in soil at the Hanford Site, a site‐specific definition of the biologically active zone is needed to identify the depth to which remedial actions should be taken to protect the environment and avoid excessive cleanup expenditures. This definition may then be considered in developing a point of compliance for remediation in accordance with existing regulations. Under the State of Washington Model Toxic Control Act (MTCA), the standard point of compliance for soil cleanup levels with unrestricted land use is 457 cm (15 ft) below ground surface. When institutional controls are required to control excavations to protect people, MTCA allows a conditional point of compliance to protect biological resources based on the depth of the biologically active zone. This study was undertaken to identify and bound the biologically active zone based on ecological resources present at the Hanford Site. Primary data were identified describing the depths to which ants, mammals, and plants may exploit the surface soil column at the Hanford Site and other comparable locations. The maximum depth observed for harvester ants (Pogonomyrmex spp.) was 270 cm (8.9 ft), with only trivial excavation below 244 cm (8 ft). Badgers (Taxidea taxus) are the deepest burrowing mammal at the Hanford Site, with maximum burrow depths of 230 cm (7.6 ft); all other mammals did not burrow below 122 cm (4 ft). Shrubs are the deepest rooting plants with rooting depths to 300 cm (9.8 ft) for antelope bitterbrush (Purshia tridentata). The 2 most abundant shrub species did not have roots deeper than 250 cm (8.2 ft). The deepest rooted forb had a maximum root depth of 240 cm (7.9 ft). All other forbs and grasses had rooting depths of 200 cm (6.6 ft) or less. These data indicate that the biologically active soil zone in the Hanford Central Plateau does not exceed 300 cm (9.8 ft), the maximum rooting depth for the deepest rooting plant. The maximum depth at which most other plant and animal species occur is substantially shallower. Spatial distribution and density of burrows and roots over depths were also evaluated. Although maximum excavation by harvester ants is 270 cm (8.9 ft), trivial volume of soil is excavated below 150 cm (∼5 ft). Maximum rooting depths for all grasses, forbs, and the most abundant and deepest rooting shrubs are 300 cm (9.8 ft) or less. Most root biomass (>50–80%) is concentrated in the top 100 cm (3.3 ft), whereas at the maximum depth (9.8 ft), only trace root biomass is present. Available data suggest a limited likelihood for significant transport of contaminants to the surface by plants at or below 244 cm (8 ft), and suggest that virtually all plants or animal species occurring on the Central Plateau have a negligible likelihood for transporting soil contaminants to the surface from depths at or below 305 cm (10 ft). Integr Environ Assess Manag 2015;11:150–160. © 2014 SETAC